To graph and solve the system of equations given by:
- \( y = \frac{2}{3}x - 2 \) (blue line)
- \( y = -\frac{1}{2}x + 5 \) (red line)
Step 1: Graph the equations
For the blue line: \( y = \frac{2}{3}x - 2 \)
-
Y-intercept: Set \( x = 0 \): \[ y = \frac{2}{3}(0) - 2 = -2 \] So the point is \( (0, -2) \).
-
X-intercept: Set \( y = 0 \): \[ 0 = \frac{2}{3}x - 2 \implies \frac{2}{3}x = 2 \implies x = 3 \] So the point is \( (3, 0) \).
Using these two points, draw the blue line.
For the red line: \( y = -\frac{1}{2}x + 5 \)
-
Y-intercept: Set \( x = 0 \): \[ y = -\frac{1}{2}(0) + 5 = 5 \] So the point is \( (0, 5) \).
-
X-intercept: Set \( y = 0 \): \[ 0 = -\frac{1}{2}x + 5 \implies \frac{1}{2}x = 5 \implies x = 10 \] So the point is \( (10, 0) \).
Using these two points, draw the red line.
Step 2: Find the intersection point (solution to the system)
To find the solution to the system, set the two equations equal to each other:
\[ \frac{2}{3}x - 2 = -\frac{1}{2}x + 5 \]
To eliminate the fractions, multiply through by 6 (the least common multiple of 3 and 2):
\[ 6 \left(\frac{2}{3}x\right) - 6(2) = 6 \left(-\frac{1}{2}x\right) + 6(5) \]
This simplifies to:
\[ 4x - 12 = -3x + 30 \]
Combine like terms:
\[ 4x + 3x = 30 + 12 \] \[ 7x = 42 \] \[ x = 6 \]
Now substitute \( x = 6 \) back into either equation to find \( y \):
Using the blue line equation: \[ y = \frac{2}{3}(6) - 2 = 4 - 2 = 2 \]
So the intersection point is \( (6, 2) \).
Summary
The solution to the system of equations is \( (6, 2) \), which is the point where the blue line intersects the red line.